State of the art review on physiochemical and engineering characteristics of fly ash and its applications - Ram A.K.; Mohanty S. (My University, 2025)
The focus of this study is to critically review the physiochemical and engineering properties of the fly ash and its applications in various fields. The utilization of fly ash has become a widespread area, but the amount of utilization is still a serious issue. It has many beneficial qualities (such as pozzolanic property, fineness, spherical shape, lightweight, etc.), which enhance its properties and make it suitable for its utilization as a new construction material. For the bulk utilization of fly ash, it should be employed in the areas independent of any other parameters. So that, the disposal problem can be reduced significantly. The knowledge of its physiochemical characteristic helps in the judgment of appropriate fly ash for any particular type of work. Fly ash can be utilized in other areas such as asphalt concrete, geopolymer concrete, ground improvement, agricultural sector, roller compacted concrete, brick, etc. that will reduce the existing ashes, and also the disposal problem can be solved appreciably. The implementation of fly ash must be avoided below the natural ground water level and below 4 °C temperature conditions. © 2022, The Author(s).